COST Action TU1404: recent advances of the Extended Round Robin Test RRT+ - Serdar, Marijana (2017)
The Extended Round Robin Testing program (RRT+) is used in the Working Group 1 (WG1) of COST Action: i) to validate advanced and non-standardised experimental techniques for testing cement-based materials, ii) to benchmark different sustainable variations of concrete mixes prepared with mineral admixtures, recycled materials and/or byproducts, and iii) to gather the range of input properties for the mixes studied at different scales (paste, mortar and concrete) which could serve designers and engineers to better predict lifespan, durability, and serviceability of concrete structures. The RRT+ is divided into two phases: the Initial Phase, which was completed in March 2016, and the Main Phase, which started in November 2016. This paper describes the organization and the current progress of the Main experimental phase. Besides, it gives an outlook on the continuation of the work and future actions.